Negros em Cuba : tensões, desafios e lutas - Marcelo Martins Lazzarin (2021)
This is a study on the tensions, struggles and challenges of the black people in Cuba and their trajectories in the face of practices of racism and anti-racism during the Colony, the Republic and the Revolution. In this way, the time frame of the research crosses three centuries of history. Racial tensions involving blacks and blacks in Cuba have been occurring since the European invasion of the Caribbean and America and the arrival of millions of enslaved people who compulsorily came to this side of the Atlantic in the African Diaspora. I analyzed part of the sociological and anthropological production about blacks in Cuba and talked to researchers, citizens and leaders of Afro-Cuban religions during the trip I made to the Island. The existence of the other, of other cosmologies, of other deities, in many cases, were used as a justification for the violence, inequality and dehumanization of individuals and nations. The spiritual, physical and symbolic elements of the various ethnic groups that landed on the Cuban coasts and the resignification of their values, their practices, their traditions, their cosmologies, in addition to the relationship with ancestry were and are fundamental to their (re) existence in the face of oppressors . These are some of the aspects that cross the temporalities of Afrocubans and Afrocubans. Even today, blacks in Cuba are fighting for the decolonization of many practices and many thoughts, which persist in acts of racism, oppression, silencing and disagreement on the island. The tensions surrounding the Afro-Cuban religions are an example of this. The study addressed the struggle of black people in Cuba against physical and symbolic violence and analyzed practices of (de) colonization, which reflect historical antagonisms.